Development of Community Network for Sustainable Tourism based on the Green Economy Concept - PHOOCHINDA, Wisakha (Journal of Environmental Management and Tourism; Vol 9 No 6 (2018): JEMT Volume IX Issue 6(30) Fall 2018DO - 10.14505//jemt.9.6(30).13, 2019)
The “Green Economy” concept is a tool that leads to the guideline to develop sustainable economy in parallel with social development, quality of life, and the balanced conservation of natural resources and the environment (Office of Agricultural Economics, 2013). The concept of economic development leading to sustainable development or Green Economy is a concept of business operation based on low carbon emission, reduction of energy consumption, promotion of efficient use of resources, leading to business growth, social development, reduced destruction of the environment and the ecosystem diversity. Tourism is a form of service business that is crucial to Thailand’s economic and social development. It has high potential to accommodate free trade and demand of global market in accordance with the National Economic and Social Development Plans. Moreover, it generates employment and income from foreign currency. However, if the rapid growth of tourism lacks good management, the environment will be directly affected. For example, energy consumption in communication and transport sectors, trips, hotel rooms, as well as garbage and waste from tourism activities. Tourism industry consists of numerous types of business, including direct, indirect, and supporting businesses, service purchased by both Thai and foreign tourists, leading to spending flows that benefit many jobs, and social stability at communal, local, and national levels (Chantouch Wannathanom 2009, 101). It illustrates the role of community tourism in generating widespread employment and occupation such as local handicrafts, agricultural and natural resources-based products, to stimulate production and maximum use of the country’s resources. At present, the government has formulated clear policy to promote and support tourism with directly responsible agencies at regional, national, and particularly community levels. The agencies with important role in community tourism include provincial administrative organizations, sub-district administrative organizations or municipalities, and community enterprises. Moreover, local administrative organizations and especially community enterprises also have the authority, duty, and role to promote and manage tourism leading to the development of sustainable tourism. Therefore, the good management of tourism business should grow in parallel with efficient environmental management from all relevant sectors especially community tourism. The management starts from small units including people, community leaders, local administrative organizations, and community enterprises. It will succeed if all stakeholders possess appropriate knowledge, if tourism development is aligned with strategic plans on provincial development, development plans of local administrative organizations, and implementation plans derived from joint planning, cooperation, awareness and conscience of community, organizations in community, and community enterprises. The community enterprises supporting Thailand’s tourism activities are scattered in all regions in the form of grouping of local wisdom, community culture, raw materials, or various resources to increase value added of products and services to generate income to the community. The management of community network for sustainable tourism based on the Green Economy is to study potentials and limitations of Thailand’s tourist destinations, role of participation of community network from tourism management, analyze knowledge and impact from operation, as well as recommendations of the guideline to develop sustainable tourism based on the Green Economy using the base of main resource which is community network allowing one to know about the context of preparedness, potentials, and limitations of community to manage tourism. The research will result in community network with systematic management, network format, or guideline to connect the network of stakeholders, resulting in management of sustainable tourism, and community’s self-reliance. Tourism entrepreneurs, both local and non-local, can use the information to develop tourist destinations in line with national policy. It also benefits those involved in formulation of policy, plans, or products for economic, social, and environmental development by the community in sustainable tourist destinations.